Wiley 5G Ref 2020
DOI: 10.1002/9781119471509.w5gref226
|View full text |Cite
|
Sign up to set email alerts
|

Development Challenges of Millimeter‐Wave 5G Beamformers

Abstract: Beamforming is the central concept that can make millimetre-wave (mmWave) a viable solution by solving challenges of link-budget, cost, power, form factor, complexity, regulatory constraint and so on. Before deployment of mmWave beamforming solution for 5G, and possibly beyond, several fundamental questions need to be answered. Some of them include hardware constraints, performance matrices, realistic propagation channel models including impairments due to obstacles such as body, blockages due to casings, phas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 103 publications
0
5
0
Order By: Relevance
“…Additionally, the widespread adoption of virtual reality (VR), augmented reality (AR), and mixed-reality (MR) technologies, which leverage high-resolution imaging, is anticipated. These immersive technologies rely on high-resolution imaging and real-time data streaming, requiring a communication infrastructure capable of delivering high-quality content with minimal latency [ 12 , 13 , 14 , 15 , 16 ]. Hence, mm-wave communication systems have played a pivotal role in achieving high data rates, benefiting from the extensive available spectrum at higher frequencies.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, the widespread adoption of virtual reality (VR), augmented reality (AR), and mixed-reality (MR) technologies, which leverage high-resolution imaging, is anticipated. These immersive technologies rely on high-resolution imaging and real-time data streaming, requiring a communication infrastructure capable of delivering high-quality content with minimal latency [ 12 , 13 , 14 , 15 , 16 ]. Hence, mm-wave communication systems have played a pivotal role in achieving high data rates, benefiting from the extensive available spectrum at higher frequencies.…”
Section: Introductionmentioning
confidence: 99%
“…The 5G is becoming a reality after deploying it by some of the main cities in the world. Millimeter-wave (mm-wave) communications play a crucial role in the 5G networks owing to its enormous available bandwidth [4]. Recent studies have confirmed a need for a fundamental change in the system architecture and radio technology to fulfill 5G goals [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…10 Department of Electrical Engineering, University of Engineering and Technology, Peshawar 25000, Pakistan. 11 Department of Electric, Electronic and Communication Engineering and the Institute of Smart Cities, Public University of Navarre, 31006 Pamplona, Spain. 12 Tecnologico de Monterrey, School of Engineering and Sciences, 64849 Monterrey, Mexico.…”
mentioning
confidence: 99%
“…Consequently, the number of antennas required needs to be increased. This increases the associated electronics with each antenna elements making the overall array very expensive compared to its lower frequency counterpart 11 .…”
mentioning
confidence: 99%